High-Intensity Intermittent Exercise and its Effects on Heart Rate Variability and Subsequent Strength Performance - Panissa, Valéria L. G.; Cal Abad, Cesar C.; Julio, Ursula F.; Andreato, Leonardo V.; Franchini, Emerson (Frontiers in Physiology, 2016)
Prupose: To investigate the effects of a 5-km high-intensity interval exercise (HIIE) on heart rate variability (HRV) and subsequent strength performance. Methods: Nine trained males performed a control session composed of a half-squat strength exercise (4 × 80% of one repetition maximum—1 RM) in isolation and 30-min, 1-, 4-, 8-, and 24-h after an HIIE (1-min at the velocity peak:1-min passive recovery). All experimental sessions were performed on different days. The maximum number of repetitions (MNR) and total weight lifted (TWL) during the strength exercise were registered in all conditions; in addition, prior to each session, HRV were assessed [beat-to-beat intervals (RR) and log-transformed of root means square of successive differences in the normal-to-normal intervals (lnRMSSD)]. Results: Performance in the strength exercise dropped at 30-min (31%) and 1-h (19%) post-HIIE concomitantly with lower values of RR (781 ± 79 ms; 799 ± 134 ms, respectively) in the same recovery intervals compared to the control (1015 ± 197 ms). Inferential analysis did not detect any effect of condition on lnRMSSD, however, values were lower after 30-min (3.5 ± 0.4 ms) and 1-h (3.3 ± 0.5 ms) with moderate and large effect sizes (0.9 and 1.2, respectively) compared with the control condition (3.9 ± 0.4 ms). Conclusion: Both RR and lnRMSSD seem to be associated with deleterious effects on strength performance, although further studies should be conducted to clarify this association.